2015
DOI: 10.2298/vsp1501021j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of disease activity on functional capacity in patients with rheumatoid arthritis

Abstract: Functional status evaluated by the HAQ is a standard for as- sessment of RA due to its convenience and good correlation with parameters of disease activity. The most significant factors that increase the odds that the patient has the greatest functional damage are DAS28 SE, DAS28 CRP and the pres- ence of CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…A study assessing functional disability in women with RA found that all the participants needed assistive devices to carry out normal daily tasks, most frequently for eating, gripping, and hygiene (Nordenskiold and Grimby, 1997). Our unadjusted regression results agree with studies that find CRP concentration to be related to functional impairment in individuals with RA (Jovanovic et al, 2015; Lisitsyna et al, 2013). One study found that CRP concentrations were significantly related to severe pain perception in RA patients, which likely impacts their ability to perform tasks (Lisitsyna et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study assessing functional disability in women with RA found that all the participants needed assistive devices to carry out normal daily tasks, most frequently for eating, gripping, and hygiene (Nordenskiold and Grimby, 1997). Our unadjusted regression results agree with studies that find CRP concentration to be related to functional impairment in individuals with RA (Jovanovic et al, 2015; Lisitsyna et al, 2013). One study found that CRP concentrations were significantly related to severe pain perception in RA patients, which likely impacts their ability to perform tasks (Lisitsyna et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…One study found that CRP concentrations were significantly related to severe pain perception in RA patients, which likely impacts their ability to perform tasks (Lisitsyna et al, 2013). Jovanovic et al reported that the presence of elevated CRP concentrations increased the odds of having the most severe functional status impairment assessed using the HAQ (Jovanovic et al, 2015). However, since inflammation is associated with adiposity, including BMI in our adjusted model likely influenced the significance of the CRP concentration coefficient (Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Female sex was associated with worse disability in this study, which is consistent with the prior studies 6,11 . Not unexpectedly, patients with RF/CCP-positive status as a marker of severe disease experienced increasing FD over the RA duration, a finding consistent with previous observations in some studies [14][15] , but not in others 8 .…”
Section: Discussionsupporting
confidence: 89%
“…Finding women to have increased HAQ-DI and DAS28 scores was not presented in other studies and warrants further investigation. As HAQ-DI and pain are measures of functional status as well as disease activity, a strong correlation between measures of disease activity exhibited significant correlation with one another (not shown) supports previous evidence of a relationship between high CRP scores and decreased functional status (Berube et al, 2017; Jovanovic et al, 2015) and patient report of pain (Lisitsyna et al, 2013).…”
Section: Discussionsupporting
confidence: 83%